Influence of Udder Morphological Traits on Milk Parameters in Healthy Sahiwal and Crossbred Cattle - Maiti, Abhinaba; Huozha, Ruokuobeinuo; Thakur, Swati; Patel, Mayank; Salaria, Ameeta; Ambwani, Tanuj; Kumar, Sudhir (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Ten each healthy lactating Sahiwal and crossbred cows were selected from the University Instructional Dairy Farm. Milk samples was collected without any preservative from lactation stage; early (30-90±15 days), mid (100-180±15 days) and late (200-280±15 days) and analysed for milk composition using Ultrascan milch analyser, enumeration of somatic cell and differential leucocyte counts by modified May-Grünwald and Giemsa staining techniques. Udder morphological traits of mammary teat shape (cylindrical, conical, bottle) and udder shape (round, bowl, trough) were done before milking. Test day milk yield was recorded highest in round shaped followed by bowl and least in trough udder shape. Round udder and cylindrical teat shape had significantly (p
Keywords: Dairy cattle; Lactation; Milk; Udder morphology